2018
DOI: 10.1177/0300985818794247
|View full text |Cite
|
Sign up to set email alerts
|

Review: Update on Classical and Atypical Scrapie in Sheep and Goats

Abstract: Scrapie is a naturally occurring transmissible spongiform encephalopathy (TSE) or prion disease of sheep and goats. Scrapie is a protein misfolding disease where the normal prion protein (PrP C) misfolds into a pathogenic form (PrP Sc) that is highly resistant to enzymatic breakdown within the cell and accumulates, eventually leading to neurodegeneration. The amino acid sequence of the prion protein and tissue distribution of PrP Sc within affected hosts have a major role in determining susceptibility to and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 171 publications
(235 reference statements)
1
50
0
1
Order By: Relevance
“…More than 50 polymorphisms in the goat prion protein-coding gene were reported worldwide 25 . A recent study on Ethiopian goat population reported six variants in Western Highland, Central Highland, and Long Eared Somali breeds of Ethiopia www.nature.com/scientificreports www.nature.com/scientificreports/ Silent substitution at codon S138 was observed in 29% of Afar, 31% of Arsi-Bale(present study) and 15% of Tanzanian goat breeds 23 .…”
Section: Discussionmentioning
confidence: 99%
“…More than 50 polymorphisms in the goat prion protein-coding gene were reported worldwide 25 . A recent study on Ethiopian goat population reported six variants in Western Highland, Central Highland, and Long Eared Somali breeds of Ethiopia www.nature.com/scientificreports www.nature.com/scientificreports/ Silent substitution at codon S138 was observed in 29% of Afar, 31% of Arsi-Bale(present study) and 15% of Tanzanian goat breeds 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in this study all samples were taken from sheep carrying the same PRNP genotype (ARQ/ARQ) and it is critical to extend this analysis to blood samples taken from other genotypes. It is well established that PRNP genotypes in sheep influence susceptibility to scrapie and likely determine different clinical and pathological phenotypes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Prion diseases are a group of fatal and infectious neurodegenerative disorders that include Creutzfeldt–Jacob disease in humans, bovine spongiform encephalopathy in cattle, scrapie in sheep and goat, and chronic wasting disease in cervids. Disease manifestation in human prion disorders can be sporadic, familial, or acquired by infection ( 1 5 ), whereas in animals acquired prion diseases prevail ( 6 9 ). Pathological hallmarks of prion diseases are vacuolation caused by neuronal death, PrP Sc plaque deposition, astrogliosis, and spongiform degeneration ( 10 ).…”
mentioning
confidence: 99%